2022
DOI: 10.3389/fphar.2022.913367
|View full text |Cite
|
Sign up to set email alerts
|

Trilobatin, a Naturally Occurring Food Additive, Ameliorates Exhaustive Exercise-Induced Fatigue in Mice: Involvement of Nrf2/ARE/Ferroptosis Signaling Pathway

Abstract: Nrf2-mediated oxidative stress is a promising target of exhaustive exercise-induced fatigue (EEIF). Trilobatin (TLB) is a naturally occurring food additive with antioxidant effect and Nrf2 activation potency. The present study aimed to investigate the effect of TLB on EEIF and elucidate its underlying mechanism. Our results showed that TLB exerted potent anti-EEIF effect, as reflected by the rope climbing test and exhaustive swimming test. Moreover, TLB also effectively reduced the levels of lactate, creatine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Frontiers in Molecular Biosciences frontiersin.org Braake et al, 2008;Sikalidis et al, 2014;Sun et al, 2018;Xu Y. et al, 2022). In addition to the above-mentioned cysteine, glutamate is another essential amino acid for GSH synthesis, and glutaminolysis is one of its sources (Whillier et al, 2011).…”
Section: Amino Acid Metabolism and Ferroptosismentioning
confidence: 99%
See 4 more Smart Citations
“…Frontiers in Molecular Biosciences frontiersin.org Braake et al, 2008;Sikalidis et al, 2014;Sun et al, 2018;Xu Y. et al, 2022). In addition to the above-mentioned cysteine, glutamate is another essential amino acid for GSH synthesis, and glutaminolysis is one of its sources (Whillier et al, 2011).…”
Section: Amino Acid Metabolism and Ferroptosismentioning
confidence: 99%
“…Another study showed that the ferroptosis-related gene CISD1 is anticipated to become one of the novel biomarkers for predicting the prognosis of breast cancer patients, thereby providing a new target for cancer therapy (Wang D. et al, 2021) (Figure 2). such as sarcopenia, RML, RMS, and EEIF (Guerrero-Hue et al, 2019;Dachert et al, 2020;Huang et al, 2021;Xiao et al, 2022). Therefore, we summarized the functions of ferroptosis in the pathogenesis of these skeletal muscle diseases.…”
Section: Cdgsh Iron Sulfur Domainmentioning
confidence: 99%
See 3 more Smart Citations